NRAS-mutant melanoma: current challenges and future prospect - Muñoz-Couselo, Eva (Onco Targets Ther, 2017)
Melanoma is one of the most common cutaneous cancers worldwide. Activating mutations in RAS oncogenes are found in a third of all human cancers and NRAS mutations are found in 15%–20% of melanomas. The NRAS-mutant subset of melanoma is more aggressive and associated with poorer outcomes, compared to non-NRAS-mutant melanoma. Although immune checkpoint inhibitors and targeted therapies for BRAF-mutant melanoma are transforming the treatment of metastatic melanoma, the ideal treatment for NRAS-mutant melanoma remains unknown. Despite promising preclinical data, current therapies for NRAS-mutant melanoma remain limited, showing a modest increase in progression-free survival but without any benefit in overall survival. Combining MEK inhibitors with agents inhibiting cell cycling and the PI3K–AKT pathway appears to provide additional benefit; in particular, a strategy of MEK inhibition and CDK4/6 inhibition is likely to be a viable treatment option in the future. Patients whose tumors had NRAS mutations had better response to immunotherapy and better outcomes than patients whose tumors had other genetic subtypes, suggesting that immune therapies – especially immune checkpoint inhibitors – may be particularly effective as treatment options for NRAS-mutant melanoma. Improved understanding of NRAS-mutant melanoma will be essential to develop new treatment strategies for this subset of patients with melanoma.